1992
DOI: 10.1128/jb.174.19.6270-6276.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of site-directed mutations on processing and activities of penicillin G acylase from Escherichia coli ATCC 11105

Abstract: Penicillin G acylase from Escherichia coli ATCC 11105 is synthesized from its precursor polypeptide into a catalytically active heterodimer via a complex posttranslational processing pathway. Substitutions in the pair of aminoacyl residues at the cleavage site for processing the small and large subunits were made. Their processing phenotypes and penicillin G acylase activities were analyzed. By the introduction of a prolyl residue at either position, the processing of the small subunit was blocked without a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
0
38
0
2
Order By: Relevance
“…One of the conformations revealed that Ser264 in the active site is positioned such that its Og group could attack the appropriate carbonyl carbon atom of the scissile bond. Moreover, this active site Ser264 is absolutely essential for activity (Choi et al 1992). Strikingly, from the structure, there was no obvious candidate for the general base in the proteolytic reaction (Hewitt et al 2000).…”
Section: Penicillin G Acylase Precursormentioning
confidence: 99%
“…One of the conformations revealed that Ser264 in the active site is positioned such that its Og group could attack the appropriate carbonyl carbon atom of the scissile bond. Moreover, this active site Ser264 is absolutely essential for activity (Choi et al 1992). Strikingly, from the structure, there was no obvious candidate for the general base in the proteolytic reaction (Hewitt et al 2000).…”
Section: Penicillin G Acylase Precursormentioning
confidence: 99%
“…These enzymes, therefore, have been termed N-terminal nucleophile (Ntn) hydrolases (19). This N-terminal residue is cysteine in glutamine-5-phosphoribose-1-pyrophosphate amidotransferase (20), glucosamine-6-phosphate synthase (21), and asparagine synthase (22); serine in penicillin acylase (23,24); and threonine in glycosylasparaginase (25,26), all proteasomes, and their bacterial homologue HslVU (27). A variety of observations indicate that proteasomes indeed cleave peptide bonds by this unusual mechanism, in which a hydroxyl group of the N-terminal threonine serves as the catalytic nucleophile: (i) replacement of this threonine by an alanine in archaeal (28) and yeast (29 -32) proteasomes abolishes their proteolytic activity; (ii) the hydroxyl group of this threonine is modified by irreversible inhibitors lactacystin (33,34), 3,4-dichloroisocoumarin (10,35), and vinyl sulfone (36); and (iii) it has been shown by x-ray diffraction to form a hemiacetal bond with the peptide aldehyde inhibitor (9,34).…”
mentioning
confidence: 99%
“…It was revealed that both Thr 263 and Ser 264 were crucial for the first cleavage of PGA. Substitution of Ser 264 with Thr, Arg, or Gly resulted in the complete failure of enzyme activation (39). Substitution of Thr 263 with Ser or Cys had less effect on the first cleavage but substitution with Gly also resulted in the failure of the normal first cleavage between Thr 263 and Ser 264 .…”
Section: Substitution Of the Ntn Serine Simultaneously Affected The Smentioning
confidence: 97%
“…Specific Binding and Covalent Binding for the Second Cleavage-In the previous studies, besides CA, PGA and PvdQ were confirmed to be Ntn hydrolases that require two-step proteolysis for activation, releasing spacers consisting of 54, 22, or 23 aa, respectively (39,40) (Table 4). The long distances between the second cleavage sites and the Ntn Ser residues were also observed in the respective crystal structures (7,41).…”
Section: Discussionmentioning
confidence: 99%